2005
DOI: 10.1177/106591290505800408
|View full text |Cite
|
Sign up to set email alerts
|

Bias in Newspaper Photograph Selection

Abstract: Previous research has shown that visual images of political candidates can influence voter perceptions. This study examines newspaper photographs of candidates to determine whether the favorableness of these pictures is related to the “political atmosphere” of individual newspapers. In particular, we examine 435 candidate photographs from several races covered by seven newspapers during the 1998 and 2002 general election seasons. Based on our analysis, we conclude that candidates endorsed by a particular newsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 33 publications
2
32
0
1
Order By: Relevance
“…The results of our experiment indicate that varying the favorableness of simply one newspaper photograph can alter the impressions of a political candidate and the likelihood of voting for that candidate. The significance of this finding is magnified by evidence from our previous study that newspapers consistently publish more favorable photographs of their preferred candidate during the course of a given campaign (Barrett and Barrington 2005). Readers of a particular newspaper are thus generally not exposed to one but rather to a series of favorable or unfavorable candidate photographs that can help to create a particular impression of a candidate and then reinforce that impression.…”
Section: Resultsmentioning
confidence: 90%
“…The results of our experiment indicate that varying the favorableness of simply one newspaper photograph can alter the impressions of a political candidate and the likelihood of voting for that candidate. The significance of this finding is magnified by evidence from our previous study that newspapers consistently publish more favorable photographs of their preferred candidate during the course of a given campaign (Barrett and Barrington 2005). Readers of a particular newspaper are thus generally not exposed to one but rather to a series of favorable or unfavorable candidate photographs that can help to create a particular impression of a candidate and then reinforce that impression.…”
Section: Resultsmentioning
confidence: 90%
“…Gibson and Zillmann (2000) argue that the items highlighted in photographs can affect how readers' perceive the organizations being featured in the pictures. They conclude that organizations should strive for candid photographs rather than staged ones (Barrett and Barrington, 2005). Additionally, scholars have suggested that organizational photographs should focus more on people actively using an organization's goods or services rather than photographs of the goods or services themselves (Henley, 2001) and that organizations should strive for gender and racial diversity in their photographs to demonstrate their inclusiveness (Kinzey, 2000).…”
Section: Publicity Photographs and Media Relationsmentioning
confidence: 97%
“…To appeal to the majority of their readers, newspapers in communities supportive of the president should write more extensively and glowingly about his visits compared with newspapers whose readers largely politically oppose him. Likewise, media organizations differ with respect to their own political leanings, as evidenced by editorial endorsements, which could affect their coverage (Barrett & Barrington, 2006). The availability of local opposition politicians also varies from community to community.…”
Section: Expected Differences In News Coverage Of Presidential Domestmentioning
confidence: 99%
“…3. Editorial bent of individual newspapers: As a number of scholars have argued or shown, the editorial bent or political atmosphere of a newsroom may influence the coverage of political figures (Barrett & Barrington, 2006;Kahn & Kenney, 2002;Page, 1996;Rowse, 1957). To test this proposition, we developed a measure of the editorial bent of each local newspaper in our study using their endorsements of candidates in both the 2000 and 2004 presidential elections, the two elections surrounding the year we examine.…”
Section: Examining Differences Across Local Newspaper Coveragementioning
confidence: 99%